Efektivitas Pengelolaan Modal Dan Tenaga Kerja Terhadap Peningkatan Pendapatan Pada Home Industry Tape Ketan Dan Tape Singkong Di Kecamatan Simpang Empat Batulicin Kalimantan Selatan - Yudhistira Dharma Arari Assadiqi; Muhammad Yasin (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2023)
This study aims to analyze the relationship between capital management and labor to increase income, analyze the effectiveness of capital management on income, and analyze the effectiveness of labor management on income in the Tape Ketan and Tape Cassava home industries in Simpang Empat Batulicin District, South Kalimantan. This study uses quantitative data types. Both secondary and primary data were used in this study, with a questionnaire serving as the primary data collection tool. Fifty individuals were randomly selected from the Ketan Tape and Cassava Tape home industry in the Simpang Empat Batulicin District of South Kalimantan. In this study, we used multiple linear regression analysis to look at the data and the F-test, t-test, and R2 statistic to test our hypothesis. Y=2.964+0.424X1+0.544X2+e is the answer to the multiple linear regression analysis. While the F test and t test to calculate the independent variables capital (X1) and labor (X2) have a partial effect on the income variable (Y) of the tape and tapioca home industry in Simpang Empat Batulicin sub-district, South Kalimantan. This study comes to the conclusion that all capital independent variables (X1) and labor (X2) affect the income variable (Y) in the Ketan Tape and Cassava Tape Home Industry in Simpang Empat Batulicin District, South Kalimantan Province, in a way that is both partial and simultaneous.